Strategic Orientation and Organisational Culture in Polish Public Organisations: Insights from the Miles and Snow Typology = Orientacja strategiczna i kultura organizacyjna w polskich organizacjach publicznych: wnioski płynące z typologii Miles'a i Snow'a - Wronka-Pośpiech, Martyna; Frąckiewicz-Wronka, Aldona (Zielona Góra: Faculty of Economics and Management Press)
Polish public organisations are often perceived as having strong bureaucratic orientation, avoiding both change and risk. However, in the last decade a distinct change in the management model of public organisations can be noticed. Public sector becomes an open diversified services and commercialization (Golensky and DeRuiter 1999; Zimmerman and Dart, 1998; Pollitt and Bouckaert, 2004; Walker, 2013].
Keywords: strategia; orientacja strategiczna; kultura organizacyjna; usługi społeczne; typologia Milesa i Snowa; sektor publiczny; strategy; strategic orientation; organisational culture; social services; Miles and Snow typology; public sector